Information seeking behaviour of electronic document and records management systems (EDRMS) users: implications for records management practices. Part 2 - Singh, Pauline; Klobas, J.; Anderson, K. (Records Management Association of Australia, 2008)
In the first article in this series, in the November 2007 issue of IQ, the authors described how they approached their study on whether the way RM professionals manage records in accordance with the ISO 15489 standard is consistent with the information seeking behaviour (ISB) of EDRMS users. Here, they continue their report by discussing their methodology.